Cryoconservation of Oocytes in a Patient with Breast Cancer and Intrauterine Early Pregnancy - Werling, M.; Tandler-Schneider, A.; Siemann, A.; Stief, G.; Kentenich, H. (Geburtshilfe und Frauenheilkunde, 2012)
Case Report: A 38-year-old patient newly diagnosed with invasive ductal breast cancer wished to cryoconserve her unfertilised oocytes. Stimulation was started on the 26th day of her menstrual cycle with daily administration of 300 IE hMG s. c. and a GnRH antagonist (cetrorelix 0.25 mg s. c.). The patient additionally received an aromatase inhibitor during the first 5 days of stimulation (letrozole 5 mg p. o.). Induction of ovulation occurred on the 11th day of stimulation with hCG (10 000 IE s. c.) and a GnRH agonist (triptorelin 0.2 mg s. c.). Seventeen oocytes were retrieved during follicle puncture and 11 were cryopreserved. Despite the administration of cetrotide (a GnRH antagonist) no luteolysis occurred during stimulation. A pregnancy test was therefore done on the 11th day of stimulation and the result was positive (β-HCG 3493 mIU/ml). Sonography showed an intrauterine pregnancy. The patient was in gestational week 5 + 0. The aspirated oocytes mostly showed a normal morphology (metaphase II) despite high progesterone levels during stimulation. The patient decided to terminate the pregnancy before starting adjuvant chemotherapy. Conclusion: We describe the case of a patient who underwent stimulation for cryopreservation of oocytes during a spontaneous pregnancy conceived in the same cycle just before starting stimulation. Stimulation was done over a short period using a combination of a GnRH antagonist and an aromatase inhibitor to ensure the lowest possible estradiol levels. The quality of the oocytes does not appear to have been negatively affected by the high progesterone levels of early pregnancy.
Keywords: Cryoconservation of oocytes; early pregnancy; breast cancer; midluteal protocol; aromatase inhibitor